PERSPECTIVES OF TEACHING / LEARNING LITERARY TEXT IN FFL CLASSROOM IN AN INCREASINGLY DIGITALIZED WORLD - Radhia CHERAK; Nouhad TIGANI; Radia BELLAGOUN (Universitaria Publishing House, Craiova, 2024)
A literary text is a written work that is generally created for an aesthetic or artistic purpose, rather than for purely informational or utilitarian reasons. This text is often characterized by its style, artistic expression, creativity, and thematic depth. Nowadays, it raises concerns among guardians regarding its teaching/learning in the classroom for French as a foreign language (FLE), both to refine its reading and its pedagogical approach. However, currently, many students are fascinated by cutting-edge technologies, which have become essential in their everyday lives. They also spend an increasing portion of their free time navigating on their digital devices, gradually moving away from reading, especially of literary texts. Yet, these could enrich the pedagogical resources used to learn the language and its associated culture. Consequently, this study aims to verify on the ground why students are fleeing literature? What strategies to recommend for integrating literary texts into the teaching of FLE within different French departments, in a context marked by an ever-increasing digitization?